From research misconduct to disciplinary sanction: an empirical examination of French higher education case law - Olivier Leclerc; Nicolas Klausser (Research Ethics Review)
Reporting and investigating research misconduct can lead to disciplinary proceedings being initiated, and ultimately to disciplinary sanctions being imposed on convicted scientists. The conversion of research misconduct findings into disciplinary sanctions is poorly understood. This article analyses all the disciplinary decisions handed down on appeal by the Conseil national de l'enseignement supérieur et de la recherche (CNESER) between 1991 and 2023, concerning breaches of research integrity by academics and doctoral students ( n  = 333). Three findings are highlighted. Firstly, the article describes how the CNESER sanctioned research misconduct even before the notion of research integrity became part of French law, by monitoring scientists’ compliance with “deontological rules”. Secondly, we show that assessing disciplinary fault involves evaluating a much broader set of circumstances than the mere existence of research misconduct, which can explain why the latter do not result in disciplinary sanctions or lighter sanctions. Thirdly, the research highlights situations where research misconduct is intertwined with other allegations, blurring the relative importance of these motives in the awarding of disciplinary sanctions. The article concludes with a call for greater accessibility to the disciplinary decisions handed down by universities in the first instance, as a key next step in gaining a better understanding of the disciplinary response to research misconduct.